Bibliography on PCM Thermal Energy Storage Solar Water Heating Systems - Zulkiflee, Marsya Alia (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Phase change materials (PCM) in thermal energy storage (TES) are a revolutionary technology for improving solar water heating (SWH) performance because of their substantial heat capacity even during the phase change process and their potential TES at a nearly constant temperature. There have been reports on studies of different types of materials used as PCM and TES for SWH systems with varying efficiency and performance. Thus far, this study has focussed on identifying TES materials, use in SWH technology. Then, compare the thermophysical properties of some TES materials from literature database sources also uncovers the different encapsulation techniques, used for TES materials in SWH systems. The methodology employed in this research is a quantified literature bibliography, citing relevant literature from the science database. Based on the analysis of relevant literature, paraffins, salt hydrates, and fatty acids are the most commonly used PCMs. The latent heat capacity of the three PCMs are relatively high. Paraffins are non-corrosive and non-toxic substances that can be obtained at a wide variety of temperatures. Salt hydrates prone to segregation and supercooling but they have higher thermal conductivity and density than the other materials. Paraffins and fatty acids were usually quite stable than salt hydrates. Physical methods, chemical methods, and physical-chemical techniques are the three types of microencapsulation PCM techniques available. PCMs may be used to capture and gather solar energy, ensuring that hot water is accessible throughout the day. In residential, commercial, and industrial applications, microencapsulated PCM is required in SWH systems.